Nepal : Defending Against Money Laundering: Into and Out of the Grey - Procopio, Joe (International Monetary Fund, 2018)
A story about Nepal's journey to address money laundering--how it navigated the various obstacles it faced over the years to meet international standards on anti-money laundering and combating the financing of terrorism.